On the obsolescence of human beings in sustainable development. Issue 1 (2nd January 2017) - Ehgartner, Ulrike; Gould, Patrick; Hudson, Marc
ABSTRACT: In 1956, the Jewish-German philosopher Günther Anders developed a philosophical anthropology on the technological and moral challenges of his time. Anders suggested the societal changes that arose with the industrial age opened a gap between the capability of individuals to produce machines and their ability to imagine and deal with the consequences caused by this capability. He argues that a 'Promethean gap' manifests in academic and scientific thinking and leads to an extensive trivialization of societal issues. In the face of climate change, Anders' philosophical anthropology contributes substantially to our attempts to fight climate change with innovation. Anders' description of 'apocalyptic blindness' helps us to explain why we cannot help pairing our belief in historical progress and growth with our ideas on social and environmental justice. With that said, this paper contributes to the debate on humanity 'after sustainability' by calling to mind Anders' historical theory on the outdatedness of humankind and his thoughts on our lack of imagination.